2022
DOI: 10.3389/fphar.2022.894981
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin d Alleviates Liver Fibrosis by Negatively Regulating the ROS/NLRP3 Inflammasome Through Activating the ERβ Pathway

Abstract: Background and aims: Saikosaponin d (SSd) has a steroidal structure and significant anti-inflammatory effects. The purpose of this study was to explore the mechanism underlying SSd’s inhibitory effects on liver fibrosis.Methods: Wild-type and estrogen receptor knockout (ERKO) mice were treated with CCl4 to establish liver fibrosis mouse models. The effects of SSd on hepatic fibrogenesis were studied in these mouse models. Hepatic stellate cells (HSCs) were activated by H2O2 to investigate the potential molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Based on the research reported [ 27 ], after conventional dewaxing, the sections were stained with Harris hematoxylin for 5 min and Sirius red dye for 20 min. After dehydration and transparency, the sections were photographed under a microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the research reported [ 27 ], after conventional dewaxing, the sections were stained with Harris hematoxylin for 5 min and Sirius red dye for 20 min. After dehydration and transparency, the sections were photographed under a microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Nrf2 is a key transcription factor for cell regulation of OS, which can activate the transcription and expression of downstream anti-OS-related enzymes, such as HO-1 and SOD to eliminate the abnormal accumulation of ROS in cells, thereby alleviating OS injury [ 77 , 78 ]. ROS is crucial in the stimulation of NLRP3 inflammasome, and suppression of ROS levels in cells can inhibit the stimulation of NLRP3 inflammasome [ 21 , 23 ]. It can therefore be assumed that TP protects renal podocytes by activating the Nrf2 pathway to reduce ROS levels and inhibit the NLRP3 inflammasome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has been reported that Festine reduces DN-provoked podocyte injury by inhibiting NLRP3 inflammasome [ 22 ]. In particular, ROS is an important factor in NLRP3 inflammasome activation, and inhibition of ROS levels in cells can impede NLRP3 inflammasome activation [ 21 , 23 ]. The aforementioned studies imply that the Nrf2/ROS/NLRP3 pathway may be a therapeutic target for DN.…”
Section: Introductionmentioning
confidence: 99%
“…SSD is a triterpenoid saponin extracted from the root of the Bupleurum chinensis. It has been used for the treatment of in ammation, fever, and liver cancer [25,26] . In this study, SSD and TMZ were combined to evaluate the effect of SSD on enhancing the TMZ sensibility in the treatment of GBM.…”
Section: Discussionmentioning
confidence: 99%